Common conditions of reptiles. Issue 1 (14th January 2016) - Rowland, Mark
Abstract : Reptiles are becoming increasingly popular as pets so it is important for veterinary surgeons seeing reptile patients to be able to recognise the common conditions that affect them and also to have an understanding of the various factors that may have led these animals to become ill. Only then can an appropriate diagnostic and therapeutic plan be fashioned. This article aims to describe the common conditions that occur in tortoises and turtles, lizards and snakes that are likely to be seen in practice, with some suggestions for treatment.